2017
DOI: 10.17583/ijep.2017.2414
|View full text |Cite
|
Sign up to set email alerts
|

Predictive effects of temperament on motivation

Abstract: Although temperament and motivation both reflect individual differences in what is perceived as rewarding or threatening, and what is to be approached and what avoided, respectively, we know rather little about how they are connected in educational settings. In this study, we examined how different aspects of temperament (reward and punishment sensitivities) predict the goals students seek to achieve in relation to learning and performance. In Study 1, four dimensions describing students’ temperament (sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 44 publications
15
35
0
Order By: Relevance
“…Students’ achievement goal orientations were assessed by using an instrument originally developed by Niemivirta (2002 ; Niemivirta et al, 2019 ) and validated in several previous studies (e.g., Tuominen-Soini et al, 2008 , 2012 ; Pulkka and Niemivirta, 2013 ; Rawlings et al, 2017 ; Tuominen et al, 2020b ). For the purposes of the present study, the instrument was modified to assess achievement goal orientations in mathematics and English.…”
Section: Methodsmentioning
confidence: 99%
“…Students’ achievement goal orientations were assessed by using an instrument originally developed by Niemivirta (2002 ; Niemivirta et al, 2019 ) and validated in several previous studies (e.g., Tuominen-Soini et al, 2008 , 2012 ; Pulkka and Niemivirta, 2013 ; Rawlings et al, 2017 ; Tuominen et al, 2020b ). For the purposes of the present study, the instrument was modified to assess achievement goal orientations in mathematics and English.…”
Section: Methodsmentioning
confidence: 99%
“…Individual differences and previous learning experiences regulate how the surrounding environment and feedback is interpreted (Kluger & DeNisi, 1996). Rawlings, Tapola and Niemivirta (2017) point out the importance of teachers' awareness of innate individual differences in their pupils, and reported that sensitivity to punishments and rewards in social settings may be connected to adopted learning goals. Hagger, Koch and Chatzisarantis (2015) noticed that people who are sensitive to social norms and those who are unaffected by the opinions of others benefit from positive feedback, as it supports their competence during a task.…”
Section: Feedback and Academic Well-beingmentioning
confidence: 99%
“…For example, while novelty (e.g., novel situations and social encounters) is often considered an important reward dimension, as some individuals are seen as temperamentally disposed to find it appealing and hence worth approaching, others may, instead, perceive it as threatening and respond with withdrawal or avoidance ( Rothbart and Hwang, 2005 ; Corr and Cooper, 2016 ). The company or attention of other people may likewise be experienced as rewarding or aversive ( Cloninger et al, 1993 ; Torrubia et al, 2001 ; Corr, 2013 ), although sensitivity to reward related to social interaction has not often been considered as a separate dimension (for exceptions, see, Colder et al, 2011 ; Rawlings et al, 2017 , 2020b ). Notably, neuropsychological research is increasingly recognising sensitivity to social reward (conceptualised as rejection or acceptance feedback and social approval) alongside or instead of tangible incentives, such as monetary rewards (e.g., Kujawa et al, 2014 ; Flores et al, 2015 ; Oumeziane et al, 2017 ), highlighting the importance of individual differences in this sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Interindividual reward sensitivity describes sensitivity to reward dependent on the actions and attitudes of other people, such as praise and attention, and intraindividual reward sensitivity to reward derived from one’s own actions and inner states. This dimension has occasionally been empirically observed to separate further into subdimensions, namely, enjoyment of novel situations and encounters, and enjoyment of and enthusiasm over personal successes ( Rawlings et al, 2017 ; see also, Colder et al, 2011 ). These subdimensions bear some resemblance to the BAS conceptualisation dimensions described as anticipatory, future-oriented pleasure from novelty and potential rewards, and pleasure derived from attained or immediate rewards, respectively (see, Corr and Cooper, 2016 ; Satchell et al, 2017 ; Gomez et al, 2020 ), which have been found to correlate differentially with educationally interesting constructs, for example, conscientiousness and implicit theories of intelligence ( Satchell et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation